BLOCKHOLDER OWNERSHIP, CAPITAL STRUCTURE AND MANUFACTURE COMPANY VALUE IN INDONESIA STOCK EXCHANGE - Yuliani Yuliani (Journal of Economics, Business, and Accountancy Ventura, 2012)
The capital markets have been in the emerging market category for example, the Indonesia StockExchange. In connection with this condition, it has been known that the behavior of issuers andinvestors are still relatively unstable. This behavior is quite different to market conditions in othercountries, which have become the efficient market. The number of listed companies is still relativelysmall compared to the number of listed companies on stock exchanges in developed countries. Theresearch aims to measure and to find empirical evidence, the direct effect of blockholder ownershipand capital structure on company value. It will investigate and examine the mediating effect ofcapital structure on company value. The research was conducted at manufacturing company inIndonesia Stock Exchange (IDX) for five years. This research use census sampling, with number 36of companies that were analyzed with Structural Equation Modeling (SEM). The result shows directlythe blockholder ownership does not have significant effect to company value. Capital structurehas mediating effect to the relationship between blockholder ownership and company value.This finding Explains that the indirect role of capital structure can increase of company value. Inaddition, capital structure directly has significant effect to company value.